Student-scientist collaboration in the global learning and observations to benefit the environment program - Balazinec, Marina; Radanovic, Ines (Intelektual Pustaka Media Utama, 2025)
The study aims to determine how one-year collaboration experience on a research project affects the recognition of collaboration benefits and the development of a student’s interest in science. 141 students did research projects in 33 collaborative groups with two scientists within the global learning and observations to benefit the environment (GLOBE) program, after which they filled out the 5-point Likert-scale questionnaire. Results show no significant difference in student attitudes about collaboration between gender and educational level. Extremely affirmative students think that important things about collaboration are: the positive influence on their knowledge, improving project writing skills, gaining self-confidence, and growth of the quality of the project. Students who appreciate scientists recognize that they achieve a better understanding by collaborating with them. Students have positive attitudes about future work in the field of science, especially older students. It was established that developing research projects with scientists affects students’ choice of a scientific career. Students who feel under stress, think that they achieve less understanding during the research process. Boys are focused on the negative aspects of collaboration, while girls are more focused on collaboration’s effects on their knowledge. Future studies can investigate if interest in science remains over the years, the effect of collaboration on scientific literacy and expanding basic knowledge.